Effect of increasing GleptoForte dosage in newborn pigs on sow and litter performance - Martin, Joel G.; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
Anemia susceptibility is a significant issue in newborn piglets due to fast growth rates and limited storage at birth. Gleptoferron is an iron supplement used in the injectable product Gleptoforte. The appropriate injection dosage of Gleptoforte is unknown. The research objective was to analyze the effect of increasing Gleptoforte dosage on piglet performance. A total of 28 litters were used to study the effects of increasing Gleptoforte injection dosage on pre-weaning piglet performance during the 21-d trial. A total of 56 pigs were allotted to each of the treatment groups which consisted of increasing levels of Gleptoforte to reach levels of 50, 100, 150, 200, 200 plus a booster on d 11, and a negative control receiving no iron. Weights were taken on d 11 and at weaning to calculate ADG. Blood was taken on d 3, 11, and at weaning from one barrow per treatment from each litter. Hemoglobin, Hematocrit, Serum Fe, and Total Iron Binding Capacity were the blood criteria measured. Linear and quadratic effects (p<0.005) were observed on piglet ADG from d 3 to 21 with increasing Gleptoforte dosage. The 200 mg + 100 mg injection showed no improvement in performance compared to the 200 mg treatment during all three periods. Hemoglobin and Hematocrit produced linear and quadratic effects (p<0.005) with measures increasing as dosage increased. In conclusion, 100 mg of Gleptoforte was the most effective injection level in terms of ADG. Blood criteria were improved by administering a d 11 booster of 100 mg to the 200 mg + 100 mg treatment group but there was no effect (p<0.005) on growth performance. The poorest growth performance and blood parameters were observed in the treatment group not given any supplemental iron. Data was analyzed via SAS (p<0.005)
Keywords: Fall 2017